2020
DOI: 10.1016/j.jdin.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Skin-lightening practices among shoppers in select markets in Kumasi, Ghana: A cross-sectional survey

Abstract: Background: Despite warnings about its harmful adverse effects and the implementation of regulatory bans, anecdotal reports suggest high use of skin-lightening agents in Kumasi, Ghana.Objective: To estimate the prevalence and motivation for skin-lightening agent use and nonuse among shoppers in Kumasi, Ghana.Methods: This is a cross-sectional survey of a convenience sample of shoppers in 3 of Kumasi's largest markets.Results: Of the 350 shoppers who were approached, 334 consented, for a response rate of 95%. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
2
10
1
1
Order By: Relevance
“…Equally, important insights from the present study included significant differences between gender, marital status, skin complexion, location of respondents (rural/ urban), level of education, average monthly income, occupation and skin bleaching products use. The use of skin bleaching products is associated with gender (33.1% vs 18.5% : females and males, respectively) as observed in the current study, corroborating the findings of Owusuagyei et al 24 with a 26.6% and 56.5% use among males and females, respectively. A meta-analysis study reported higher prevalence among males (28%) 30 , in contrast to our study finding and that of Owusu-agyei et al 24 , demonstrating varying proportions among populations of different settings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Equally, important insights from the present study included significant differences between gender, marital status, skin complexion, location of respondents (rural/ urban), level of education, average monthly income, occupation and skin bleaching products use. The use of skin bleaching products is associated with gender (33.1% vs 18.5% : females and males, respectively) as observed in the current study, corroborating the findings of Owusuagyei et al 24 with a 26.6% and 56.5% use among males and females, respectively. A meta-analysis study reported higher prevalence among males (28%) 30 , in contrast to our study finding and that of Owusu-agyei et al 24 , demonstrating varying proportions among populations of different settings.…”
Section: Discussionsupporting
confidence: 92%
“…The use of skin bleaching products is associated with gender (33.1% vs 18.5% : females and males, respectively) as observed in the current study, corroborating the findings of Owusuagyei et al 24 with a 26.6% and 56.5% use among males and females, respectively. A meta-analysis study reported higher prevalence among males (28%) 30 , in contrast to our study finding and that of Owusu-agyei et al 24 , demonstrating varying proportions among populations of different settings. According to Owusu-agyei et al 24 females were more likely to use skin bleaching products compared to males.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Skin bleaching became a popular cosmetic practice in many African countries in the 1950s ( Sagoe et al, 2019 ). Up to 75% of women in Nigeria ( Dadzie and Petit, 2009 , Dlova et al, 2015 ), 60% in Senegal ( Blay, 2011 ), 50% in Mali ( Baxter, 2000 ), and 30% in Ghana are estimated to use bleaching creams regularly, with similar rates in other African countries ( Lartey et al, 2017 , Mckinley, 2001 ).Throughout the continent, both men and women are frequently targeted with marketing campaigns showing public figures who bleach their skin ( Owusu-Agyei et al, 2020 ). Consequently, individuals claim that lighter skin makes them attractive and increases their career opportunities ( Dlova et al, 2015 , Yusuf et al, 2019 ).…”
Section: Regionsmentioning
confidence: 99%
“…16 The higher percentage of international products used among participants is reflective of the poorly regulated importation and access of products into developing countries of Africa. 17 Although majority of respondents were aware of the side effects of the products, quite a number of them still patronized them. For this group of individuals, perceived benefit of the products probably outweighed the risk.…”
Section: Discussionmentioning
confidence: 99%